Impairment of the Zn/Cd detoxification systems affects the ability of Salmonella to colonize Arabidopsis thaliana - Visconti, Sabina; Astolfi, Maria Luisa; Battistoni, Andrea; Ammendola, Serena (Frontiers in Microbiology, 2022)
Salmonella capacity to colonize different environments depends on its ability to respond efficiently to fluctuations in micronutrient availability. Among micronutrients, Zn, besides playing an essential role in bacterial physiology, is a key element whose concentration can influence bacterial survival in a particular niche. Plant colonization by Salmonella enterica was described for several years, and some molecular determinants involved in this host-pathogen interaction have started to be characterized. However, it is still unclear if Zn plays a role in the outcome of this interaction, as well established for animal hosts that employ nutritional immunity strategies to counteract pathogens infections. In this study, we have investigated the involvement of Salmonella Typhimurium main effectors of zinc homeostasis in plant colonization, using Arabidopsis thaliana as a model host. The results show that to colonize plant tissues, Salmonella takes advantage of its ability to export excess metal through the efflux pumps ZntA and ZitB. In fact, the deletion of these Zn/Cd detoxification systems can affect bacterial persistence in the shoots, depending on metal availability in the plant tissues. The importance of Salmonella ability to export excess metal was enhanced in the colonization of plants grown in high Zn conditions. On the contrary, the bacterial disadvantage related to Zn detoxification impairment can be abrogated if the plant cannot efficiently translocate Zn to the shoots. Overall, our work highlights the role of Zn in Salmonella-plant interaction and suggests that modulation of plant metal content through biofortification may be an efficient strategy to control pathogen colonization.